Batch‐Sprayed and Stamp‐Transferred Electrodes: A New Paradigm for Scalable Fabrication of Multilayer Dielectric Elastomer Actuators. (21st August 2022) - Cohen, Andy J.; Kollosche, Matthias; Yuen, Michelle C.; Lee, Dae‐Young; Clarke, David R.; Wood, Robert J.
Abstract: Multilayer dielectric elastomer actuators have a wide range of potential applications, but their development and commercial implementation have been hindered by existing manufacturing processes. Existing processes are low‐throughput, limited in area, and/or can only process a narrow range of elastomers. This study presents a novel fabrication paradigm that overcomes these challenges: instead of sequentially patterning electrodes directly onto successive elastomer layers, electrode stamps are patterned onto a carrier film in an independent batch‐spray process and the electrodes are then stamp‐transferred onto each elastomer layer. By modularizing the production and assembly of electrodes, a laboratory‐scale implementation of the process achieves a throughput of 15 layers h −1, a maximum electrode size of 300×300 mm, and tuning‐free compatibility with a wide range of elastomers. The batch‐spraying paradigm also provides the unique capability to evaluate and modify electrodes before they are assembled into a multilayer; a method of mechanically treating the electrodes is employed to increase the breakdown strength of Elastosil P7670 devices from 15.7 to 33.5 V µm −1 . The electrodes are conductive up to a strain of more than 200% and add negligible stiffness to the multilayer structure. The capabilities of this process to produce useful devices are demonstrated with a large‐area loudspeaker and an actuator with 60 active layers. Abstract : A new process is proposed for fabricating multilayer dielectric elastomer actuators (MDEAs). The process separates the electrode deposition process into two independent steps: batch‐spraying electrodes and then stamping them onto the elastomer surface. This allows for a higher‐throughput, larger‐area process that is compatible with a wide range of elastomers, and is a step toward commercialization of MDEAs.